2017
DOI: 10.21037/gs.2017.01.04
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative psychosocial characteristics may predict body image and sexuality two years after risk-reducing mastectomy: a prospective study

Abstract: Background: Risk-reducing mastectomy (RRM) in patients at high risk has become more available and the rates of both bilateral (BRRM) and contralateral (CRRM) procedures are increasing. For women opting for RRM, psychosocial well-being, body image and sexuality are known to be important patient-reported outcomes. The aim of the present study was to investigate baseline health-related quality of life (HRQoL) and emotional distress (anxiety and depression) as predictors of body image and sexuality two years af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 30 publications
1
16
0
Order By: Relevance
“…A small body of literature focused on sexual outcomes after breast reconstruction specifically. [4][5][6][7][8][9][10][11][12][13][14][15] Sexuality is considered a biopsychosocial concept, and therefore is thought to be associated with both biological and psychosocial factors. Some studies emphasized sexuality and body satisfaction following breast reconstruction, 5 as well as femininity and attractiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A small body of literature focused on sexual outcomes after breast reconstruction specifically. [4][5][6][7][8][9][10][11][12][13][14][15] Sexuality is considered a biopsychosocial concept, and therefore is thought to be associated with both biological and psychosocial factors. Some studies emphasized sexuality and body satisfaction following breast reconstruction, 5 as well as femininity and attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…11 Two studies have reported an association between patient characteristics and sexual outcomes after breast reconstruction: older women reported higher sexual well-being than younger women, 12 whereas better preoperative quality of life and lower emotional distress predicted higher postoperative sexual well-being. 13 The partner also plays an important role in the process of breast reconstruction; couples greatly value partner involvement and joint surgical decisionmaking. 14 Partner intimacy after breast reconstruction was found to be related to couples' adjustment and communication styles, and individual expectations.…”
Section: Introductionmentioning
confidence: 99%
“…It is emphasized by scholars that the negative body image is one of the important factors that negatively affects sexual life of women. (6,8,10,22) Also, Fang et al (22) have been reported there is a relationship between body image and sexuality, and that there are more sexual problems in people with poor body image. In current study mean scores on prior sexual adjustment indicated that women were moderately satisfied with their sexual life preBC, but that their sexual adjustment worsened (Mean=-3.79) following mastectomy/lumpectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have highlighted these problems should be identified and treated because they affect other areas of life. (10) However, when faced with serious disease such as cancer the health professionals are usually more concerned with assuring survival and restoring physical integrity. Therefore sexuality and body image assessments are not routinely provided in the oncology setting.…”
Section: • Researchmentioning
confidence: 99%
“…As a result, patients may avoid social interaction, neglect self‐care, and develop clinically significant levels of depression or anxiety. The association between psychological distress and body image has been evaluated with age, 8 primary breast surgery (mostly mastectomy), 9 risk‐reducing surgery, 10 and post‐treatment either immediately postsurgery 11 or during survivorship 9 . Around 30% of breast cancer survivors expressed body image dissatisfaction after 4 years postbreast surgery and 25% had depression, while 53% had anxiety 9 …”
Section: Introductionmentioning
confidence: 99%